The feasibility of assessing teenagers’ oral english language performance with a rubric (2014)
This article reports the experience of a study group in a public university in Colombia, formed mostly by academic coordinators who worked in the design of assessment rubrics. Its focus is on the experience of the academic coordinator of the English program for teenagers, who concentrated on implementing the rubric to assess the students’ oral performance. The data collection instruments used were the rubric and interviews with the teachers and students. The results are related to the impact of the assessment rubrics on the program’s teachers regarding practicality.En este artículo se presenta la experiencia de un grupo de estudio en una universidad pública colombiana, conformado principalmente por coordinadores académicos que trabajaron en el diseño de rúbricas para la evaluación. El presente trabajo se centra en la experiencia de la coordinadora del programa de inglés para jóvenes, quien usa las rúbricas para evaluar el desempeño oral de los estudiantes. Los instrumentos de recolección de datos fueron la rúbrica y entrevistas a los profesores y estudiantes. Los resultados están relacionados con la viabilidad y utilidad de la rúbrica.